Prevalence of chronic HBV infection in pregnant woman attending antenatal care in a tertiary hospital in Mwanza, Tanzania: a cross-sectional study - Geffert, Karin; Maponga, Tongai G.; Henerico, Shimba; Preiser, Wolfgang; Mongella, Stella; Stich, August; Kalluvya, Samuel; Mueller, Andreas; Kasang, Christa (BMC infectious diseases, 2020)
Background Tanzania has a high prevalence (7.17%) of chronic hepatitis B infection. Mother to Child transmission is very common, resulting in high rate of chronic infections. Currently, there is no screening program for HBV in pregnant women. This study investigated the prevalence and risk factors for chronic HBV infection in pregnant women in a tertiary hospital in Mwanza, Tanzania. Methods Seven hundred and forty-three women attending antenatal care and/or delivering at the Bugando Medical Centre were enrolled. All answered a questionnaire on sociodemographic and other risk factors and were tested for HBsAg using a rapid test. In HBsAg positive mothers, maternal blood and umbilical cord blood samples collected after delivery were analyzed for serological (HBsAg, HBeAg and anti-HBe) and virologic (HBV-DNA viral load and genotype) markers. All their babies were vaccinated within 24 h of delivery. The children were followed up at 3 years of age. Data was analyzed using the Mann-Whitney U-test, independent sample T-test and logistic regression. Results Of the 743 participants, 22 (3%) were positive for HBsAg, and 2 (9%) had detectable HBe-antigen. Low condom use was the only statistically significant risk factor for chronic HBV infection (OR = 3.514, 95%CI = 1.4–8.0). Of 14 maternal blood samples genotyped, 10 (71%) were genotype A and 4 (29%) were genotype D. HBV-DNA was detected in 21/22 samples, with a median of 241 IU/ml (range: 27.4–25.9 × 10 7 IU/ml). Five (33%) of 15 available cord blood samples were positive for HBsAg and 10 (67%) were negative. At follow-up, one child showed chronic HBV infection characteristics, one had anti-HBs level of 7 mIU/ml and 5/7(71%) had protective anti-HBs levels (> 10 mIU/ml). Conclusion This cohort of pregnant women showed a lower-intermediate prevalence of HBV of 3%. In the 3 years follow-up only 1 out of 7 children showed evidence of chronic HBV infection. The child’s mother with high viral load (25.9 × 10 7 IU/ml), was positive for HBeAg with a high degree of sequence similarity suggesting vertical transmission. These results highlight a need for improved diagnosis and treatment of HBV infection in pregnant women in Tanzania, in order to prevent vertical transmission.